La rappresentazione lessicografica dei femminili professionali - Emanuela Di Venuta (Culture e Studi del Sociale)
The nouns referring to women in professions or occupations offer an interesting field to analyse the linguistic representation of women, including both the sociolinguistic reflections that can be found there and the changes that have taken place in the extra-linguistic reality and historical context. The linguistic datum can be considered an indicator of the social processes to which it is linked. The present contribution presents the results of an analysis concerning the diachronic evolution of the lexicographic representation of a group of seven italian lexemes (amministratrice, avvocata, direttrice, medica, ministra, procuratrice and sindaca). The dictionary is chosen as a privileged observatory of analysis from a diachronic perspective and as a documentary resource because it gathers within it the linguistic heritage of a nation. Dictionaries attempt to describe reality, to record language but also, especially in the past, to guide its use, by placing itself between politically and linguistically correct.  The reconstruction of the lexicographic representation will make it possible to place chronologically the origin of certain stereotypes, of the overextension of the generic masculine 'prescribed', as well as the hypotheses concerning the suffixes and semantic distribution of the analysed lexemes.